The concept of 'NYAWA' - Ibrahim, Faridah Hanum; Qamaruz Zaman, Faridah (University Putra Malaysia, 2012)
NYAWA in the national language, Bahasa Malaysia, means life. NYAWA is the acronym for Nature’s Yield and Wonders of Art and is meant to depict nature’s bountiful yield i.e. biodiversity and its various functions. Biodiversity as defined in the Convention of Biological Diversity (CBD, 1992) is the variety of all forms of life ranging from the species, the genes it contains and ecosystems. Article 13 of CBD on Public Education and Awareness states this as one of its activities: Promote and encourage understanding of the importance of, and the measures required for, the conservation of biological diversity, as well as its propagation through media, and the inclusion of these topics in educational programmes. Malaysia is one of the 12 megadiversity countries in the World with 15,000 plant species, 290 mammals, 150,000 invertebrates, with insects being the largest group (e.g. butterflies-1200 species, moths-12,000 species), and 8,000 fishes (Latiff, 2008).